Identification and characterization of variants in PSEN1, PSEN2, and APP genes in Chinese patients with early-onset Alzheimer's disease - Haitian Nan; Min Chu; Deming Jiang; Wenping Liang; Yu Li; Yiming Wu; Zhe Wang; Liyong Wu (Alzheimer’s Research & Therapy)
Abstract Variants in PSEN1, PSEN2, and APP are major genetic causes of early-onset Alzheimer’s disease (EOAD). Our study aimed to identify the genotypic and phenotypic spectrums in a Chinese EOAD cohort and confirm their pathogenicity by functional analysis. This study included 304 unrelated clinically diagnosed EOAD participants of Chinese Han ancestry. Whole-exome sequencing revealed that 26 out of 304 individuals (8.6%) carried rare variants in PSEN1, PSEN2, and APP, including 16 in PSEN1 (5.3%), 6 in PSEN2 (2.0%), and 4 in APP (1.3%). Eight variants were novel, including PSEN1 p.Q56R, PSEN1 p.L174P, PSEN1 p.S289P, PSEN1 p.Y466C, PSEN2 p.R17W, PSEN2 p.F331Y, APP p.D197N, and APP p.D252V. Functional study revealed that the PS1 L174P, S289P, R377M, Y466C, PS2 V214L, and M239T mutants increased Aβ42 levels and Aβ42/Aβ40 ratios. The PS1 L174P, R377M, and Y466C mutants decreased the maturation of presenilin-1. Our findings highlight the prevalence and pathogenic significance of APP /PSENs variants in a Chinese EOAD cohort and expand the phenotypic and genotypic spectrum of EOAD.